8th Men`s European Handball Championship - 17th-27th January in Norway. Qualitative trend analysis - Hergeirsson, T. (EHF, 2008)
Although the EURO 2008 in Norway did not really present any new things in the play, there were anyhow some trends clearly to be seen throughout the Championship: • The goalkeepers were progressing especially on near shots • All the teams are using 1 or 2 defence specialists, and manage to change between defence and attack without seemly problems. This could be explained with the development of the fast retreat phase (more focus and better organised by the teams). It can also be explained with that the opponent is also interested in changing players from defence to attack and therefore not delivering pressure in fast breaks. • Some of the teams were in periods of executing team fast breaks and extended fast breaks (2nd wave) with their defence specialists, and putting pressure on the opponent before changing with the attack specialists. The Danish team was taking clear advantage of this in the semi-final and final. • There were more fast breaks now compared to 2006, especially there were more team fast breaks among the top 6 teams. • Despite more fast break attacks the efficiency is decreasing compared with EURO 2006. At the same time the number of turnovers for the top 6 teams has increased (excl. DEN). These trends could be explained by the rising efficiency of the goalkeepers` or/and by the development of the fast retreat phase. • There were matches with high-speed handball in the PR and the MR but there were some signs of tired players in the finals. One or two more rest days will most likely give the team`s better chance to recover and prepare. This will hopefully give us some more high-speed handball in the future finals • In organised attack the efficiency decreased compared with EURO 2006. • Among the top teams the most common offensive actions was transition play (3:3 to 4:2) and different variations of crossing. • The best teams have many back players that are very strong in 1:1 situations, and they are frequently drawing the attention of 2 defenders. • There were teams creating good shooting situations directly from the 9-meter throw. Especially the Croatian team with Balic as a "director". • There are still challenges for the referees in some situations in play (p.18). Players and coaches also have their responsibility on this matter.